Strategies Done By The Regional Revenue Management Agency Of Labuhanbatu Selatan Regency In Optimizing Land And Building Tax Receiving - Khairul Abdi Hasibuan (Pena Cendekia Insani, 2022)
Efforts to receive land and building taxes in South Labuhanbatu are strived to always increase every year, but in practice there are still problems, namely many people who pay less attention to paying taxes, people always wait for the due date to pay taxes, sometimes tax collectors feel difficulty in finding the address of the taxpayer to provide SPPT. This study uses a qualitative approach with data collection techniques through interviews, observations, and documentation, the informants in this study were the head of the section for determination, data management, billing and objections, PBB services, the Head of Control and the people of South Labuhanbatu. Test the validity of the data using triangulation techniques. Data analysis was carried out by data reduction, data presentation, and drawing conclusions. The results of the study show that the strategy carried out by the Regional Revenue Management Agency (PBB) to increase land and building tax revenues is quite good, which has increased for 2 years. Tax payments are made at the Bank of North Sumatra, or other E-commerce on the basis of cooperation, conducting intensive socialization and appeals to villages. The obstacle that hinders increasing PBB revenue in South Labuhanbatu so far is that taxpayers are not in place, and also taxpayers Taxes are always waiting for the due date, lack of awareness of land and building taxpayers, SIMDA applications are often problematic.